Analytical theory of attosecond transient absorption spectroscopy of perturbatively dressed systems. Issue 7 (January 2020) - Kolbasova, D; Santra, R
Synopsis: The current work provides an elementary explanation of the signals one can obtain in attosecond transient absorption experiments. We perform a perturbative analysis of the transient absorption signal as a function of the time delay between the excitation pulse and the dressing pulse. We discuss an unusual kind of experiment, where the information is gained from the absorption spectrum of an attosecond XUV pump pulse, and the probe pulse gives a reference time, allowing to measure the time evolution of a system. We illustrate our concepts through numerical calculations for a model atom.